Advanced Isotope Separation Technology for Fusion Fuel. (3rd April 2022) - Xiao, Xin; Sessions, Henry T.; Rabun, Robert
Abstract: Deuterium-tritium fusion is the easiest nuclear fusion reaction among known fusion reactions. Since tritium is extremely rare, it is artificially produced by irradiating lithium metal. The separation, isolation, and storage of the tritium isotope has been a major focus of the Savannah River Site (SRS) for many decades. Thermal diffusion, fractional absorption, and cryogenic distillation have all been used in the past, and each has significant operational and safety challenges. A process known as the Thermal Cycling Absorption Process (TCAP) was invented at SRS, and because of its overwhelming advantages in safety, efficiency, size, and reduced tritium inventory, it has replaced all other hydrogen isotope separation processes at SRS. The working principles and current development of hydrogen isotope separation using TCAP at SRS are explained as a potential advanced isotope separation process for the fusion fuel cycle.